PENERAPAN MEKANISME BONUS DAN TUNNELING INCENTIVE TERHADAP TRANSFER PRICING PERUSAHAAN - Ahmad Syuheri; Jaka Syahputra; Masnuripa Harahap; Herman P. (CV. Multi Kreasi Media, 2023)
This study aims to analyze the application of bonus mechanisms and tunneling incentives to transfer pricing. This research uses a qualitative approach with data collection techniques through literature study. The results of the study show that multinational companies as companies that have relationships with related parties will have the convenience of conducting tunneling incentives on transfer pricing transactions. This condition is an effort to avoid taxes, namely through manipulation of the tax burden. In addition, the non-tax factor that becomes the motive for tax avoidance practices is the bonus mechanism. The application of the bonus mechanism can indicate a company to practice tax avoidance because directors and management manipulate company profits with the aim of obtaining bonuses.